Synergy of Xpert (MTB/RIF) and Line probe assay for detection of rifampicin resistant strains of Mycobacterium tuberculosis - Hussain, Shahida; Sultan, Sikander; Riaz, Saba; Hussain, Hajra; Javed, Hasnain; Mazhar, Rabia (The Journal of Infection in Developing Countries, 2024)
Introduction: Early diagnosis and successful treatment of drug-resistant tuberculosis (TB) demands rapid, precise, and consistent diagnostic methods to minimise the development of resistance. Therefore, this comparative study was designed to evaluate the diagnostic performance of Xpert (MTB/RIF) and Line probe assay (LPA) for detecting drug-resistant TB. Methodology: This study comprised 389 (279 pulmonary and 110 extrapulmonary) samples from patients suspected of having TB. All samples were subjected to Xpert (MTB/RIF), LPA, solid culture, and drug-susceptibility testing. Out of 320 samples, only 180 culture (gold standard) positive were included in the final evaluation. The diagnostic characteristics for methods used were determined by calculating diagnostic sensitivity, specificity, and predictive values. The agreement between all methods was determined by calculating the kappa coefficient. Results: The sensitivity and specificity for Xpert (MTB/RIF) for detecting TB were 88.5% and 96.4%, respectively, against the solid culture. On the other hand, LPA showed sensitivity and specificity at 94.3% and 100%, respectively. Xpert (MTB/RIF) showed moderate agreement (kappa 0.65, p < 0.01) – (73.3% sensitivity; 97.6% specificity) for the detection of rifampicin resistance. However, LPA achieved better diagnostic accuracy (kappa 0.80, p < 0.01) – (84.6% sensitivity; 98.4% specificity) against drug-resistant TB. Conclusions: Xpert (MTB/RIF) and LPA have outstanding diagnostic sensitivity and specificity against RIF resistance with a shorter turnaround time, which could result in a substantial therapeutic outcome. Our findings showed LPA superiority over Xpert (MTB/RIF) for drug resistance. However, due to operational challenges, the requirement of technical expertise and infrastructure issues, LPA cannot be used as point-of-care testing in resource-limited countries.